EVALUASI ANGGARAN DAN REALISASI PENDAPATAN ASLI DAERAH PADA DINAS PENDAPATAN DAN ASSET DAERAH PROVINSI SULAWESI TENGGARA - Purnama Sari (AkMen JURNAL ILMIAH, 2012)
This study aims to determine the factors that cause the difference between Revenue Budget to Actual revenue realization in terms of budget revenues of Sulawesi Tenggara. The analysis method used is descriptive analysis of the factors explaining the cause of the difference between the Revenue budget realization. The result of this research is, generally speaking is that the realization of revenue revenue budget from 2007 to 2009 had less margin or excess revenues. The factors that cause the difference between the budget with revenue realization is not only coming from the provincial government itself, but also because of the lack of awareness of the public to pay taxes and fees on time.